Bacteriophage endolysins as a response to emerging foodborne pathogens - Oliveira, Hugo Alexandre Mendes (2012)
Continuous reports on foodborne outbreaks and increasing prevalence of antibiotic-resistant bacteria call for the development of novel preservation techniques that assure the safety of food products. Bacteriophage endolysins are highly active antibacterial peptidoglycan hydrolases that have evolved over millions of years to become the ultimate weapon against bacteria, with potential to be used as a food preservative. We here give an overview of all distinct endolysins encountered so far, we discuss their inherent qualities and review their role in preventing and controlling foodborne pathogens, divulging their potential for future applications.